Rheumatic Heart Disease Special Issue of Nepalese Heart Journal - Prajapati, Dipanker (Nepalese Heart Journal, 2016)
Rheumatic fever (RF) and Rheumatic Heart Disease (RHD) accounts for most cases of acquired heart disease in children and young adult, in the developing world. It causes considerable suffering, serious disability and premature death with significant social impact in terms of hospitalization costs and clinic visits. Prevalence is more common in areas of overcrowding and poor socioeconomic conditions. The treatment is highly influenced in our country by its geographical condition and also the lack of financial resources, but the lack of knowledge seems to be the prime factor.